On the Identity of Utricularia equiseticaulis Blatt. et McCann - Sundararaghavan, R.; Wadhwa, B. M.; Ansari, M. Y. (Indian Forester, 1970)
Utricularia equiseticaulis Blatt. et McCann, was first described from Mahabaleshwar but there is no record of its being subsequently collected ever since. A reference to the various prominent herbaria in India revealed that it is not represented in any of them. In 1967, the species was rediscovered from the type locality and critically studied. It is now evident that U. equiseticaulis is only a robust form of U. graminifolia Vahl and hence merged under the latter species.